Pensiones de jubilación en España: reformas recientes y algunas consecuencias sobre el riesgo de pobreza - Sarasa, Sebastián (Política y Sociedad, 2008)
This article describes the last reforms in the Spanish retirement pensions and how differently personal income has evolved between the young and the elder. The author concludes that poverty risk has risen among the older than 60 bacause several factors. Personal income decrease as a consequence of the growing trend to abandon labor activity among the workers older than 60. However, the most important factor in poverty risk up rising among the elder is the indexing pensions reform implemented i the 80s. Indexing pensions by prices instead of wages has widened the gap between the young and the elder incomes.